Genital image and sexual function during pregnancy: longitudinal study: Genital image and sexual function during pregnancy - Vieira Carpes Tavares , Larissa; Kilian, Cristiane; Pereira Dezan Martins Gonçalves , Ester; Huyer da Roza, Thuane; Dias , Mirella; Eleine Wolpe , Raquel; Tonon da Luz, Soraia Cristina; Júlia da Silva Honório, Gesilani (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Introduction: Pregnancy is a period of transformations that can interfere with the pregnant woman’s genital image (GI) and sexual function (SF). There may be fluctuations in GI and SF according to the gestational trimesters. However, it is still uncertain whether or not there is a decrease in these two variables throughout pregnancy. Objective: Compare GI and SF in the second and third trimester of pregnancy. Methods: The Female Genital Self-Image Scale (FGSIS) and Female Sexual Function Index (FSFI) questionnaires were applied to analyze GI and SF, respectively. Each participant answered the questionnaires in the second and third trimester of pregnancy. Quantitative variables were analyzed descriptively using simple frequencies and percentages (categorical variables), and mean and standard deviation (numeric variables). To check the normality of the data, the Shapiro-Wilk test was performed. To compare the scores obtained related to GA and SF, the Wilcoxon test was used, with a significance level of 5%. Results: 10 pregnant women were included in the study. Regarding the GI assessment, the average score on the FGSIS questionnaire for pregnant women was 22.0 (±3.6) and in the reassessment it was 14.4 (±4.5), where higher scores demonstrate a more positive GI. Furthermore, the participants’ SF had an average of 25.5 (±6.6) in the evaluation and 19.5 (±12.4) in the reevaluation, through the total score of the FSFI questionnaire, in which lower scores represent worsening from SF. In other words, from the second to the third gestational trimester, pregnant women indicated a worsening in GI and SF, except for the desire and lubrication domains. Half of the pregnant women (n=5) showed signs of sexual disfuction in the evaluation and 80% (n=8) in the reevaluation. The domains with the worst indicators were desire and orgasm. Conclusion: SF and GI showed significant worsening throughout the pregnancy cycle of pregnant women participating in this study.